2023
DOI: 10.3390/biom13030464
|View full text |Cite
|
Sign up to set email alerts
|

Surface Treatments of PEEK for Osseointegration to Bone

Abstract: Polymers, in general, and Poly (Ether-Ether-Ketone) (PEEK) have emerged as potential alternatives to conventional osseous implant biomaterials. Due to its distinct advantages over metallic implants, PEEK has been gaining increasing attention as a prime candidate for orthopaedic and dental implants. However, PEEK has a highly hydrophobic and bioinert surface that attenuates the differentiation and proliferation of osteoblasts and leads to implant failure. Several improvements have been made to the osseointegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 96 publications
0
26
0
Order By: Relevance
“…Numerous studies have shown that a 3D porous network can be formed on the PEEK surface by sulfonation. The 3D porous network not only has good osseointegration, cytocompatibility, and antibacterial properties but also can be used for the loading of biological factors and drugs . However, few studies have been devoted to investigating the formation process of the 3D porous networks and to further control the surface morphology and composition of sulfonated PEEK.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that a 3D porous network can be formed on the PEEK surface by sulfonation. The 3D porous network not only has good osseointegration, cytocompatibility, and antibacterial properties but also can be used for the loading of biological factors and drugs . However, few studies have been devoted to investigating the formation process of the 3D porous networks and to further control the surface morphology and composition of sulfonated PEEK.…”
Section: Discussionmentioning
confidence: 99%
“…These methods are usually combined according to actual situations to achieve better effects. With continuous research and the development of modification methods, the performance of PEEK implants has been continuously optimized, from initially enhancing mechanical properties and bioactivity to the stage of aspiring excellent osseointegration and anti-infection ability. , However, no widespread attention has been paid to blood vessel regeneration, which is another key process of osteogenesis . Good angiogenesis provides the necessary oxygen and nutrients at bone defect sites and is meaningful for tissue regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…However, the high hydrophobicity of PEEK inhibited the adhesion, migration, proliferation, and differentiation of osteoblasts on its surface, 13 resulting in poor bone integration ability and ultimately the failure of artificial joint implantation. 14 Meanwhile, a hydrophobic surface usually leads to direct contact between friction pairs in a lubricating medium, affecting wear resistance. 15,16 Poor tribological properties mean that it is more prone to wear, which would reduce the life of joint prostheses by causing osteolysis and bone resorption due to wear debris.…”
Section: Introductionmentioning
confidence: 99%
“…Bone binding between the implant and the human bone needs to absorb the surrounding cells to initiate when the implant is in the human body. However, the high hydrophobicity of PEEK inhibited the adhesion, migration, proliferation, and differentiation of osteoblasts on its surface, 13 resulting in poor bone integration ability and ultimately the failure of artificial joint implantation 14 . Meanwhile, a hydrophobic surface usually leads to direct contact between friction pairs in a lubricating medium, affecting wear resistance 15,16 .…”
Section: Introductionmentioning
confidence: 99%